2012
DOI: 10.1016/j.jpain.2011.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The Interruptive Effect of Pain in a Multitask Environment: An Experimental Investigation

Abstract: Daily life is characterized by the need to stop, start, repeat, and switch between multiple tasks. Here, we experimentally investigate the effects of pain, and its anticipation, in a multi-task environment. Using a task switching paradigm participants repeated and switched between three tasks, of which one predicted the possible occurrence of pain. Half of the participants received low intensity pain (N=30) and half high intensity pain (N=30). Results showed that pain interferes with the performance of a simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 48 publications
6
40
0
Order By: Relevance
“…Third, analysis of the JND data revealed that participants were less accurate in making tactile TOJs on trials in which bodily threat was induced compared to control trials. Although we had no specific hypotheses regarding the JND, this reduced accuracy in tactile TOJs following the anticipation of pain is in line with studies showing that painful somatosensory stimuli interfere with task performance (e.g., [6,27,28,34]). Forth, it should be noted that also in control trials the PSS differed significantly from the actual point of simultaneity (0ms).…”
Section: Discussionsupporting
confidence: 82%
“…Third, analysis of the JND data revealed that participants were less accurate in making tactile TOJs on trials in which bodily threat was induced compared to control trials. Although we had no specific hypotheses regarding the JND, this reduced accuracy in tactile TOJs following the anticipation of pain is in line with studies showing that painful somatosensory stimuli interfere with task performance (e.g., [6,27,28,34]). Forth, it should be noted that also in control trials the PSS differed significantly from the actual point of simultaneity (0ms).…”
Section: Discussionsupporting
confidence: 82%
“…We also showed that activities are performed less accurately and more slowly after being interrupted by pain [17]. This finding adds to existing evidence that pain impairs performance of concurrent tasks [6,8,9,27,36] and switching to new tasks [30]. Further, it parallels findings from other research fields, showing performance decrements after interruptions by pain-irrelevant demands (e.g., [5,35]).…”
Section: Introductionsupporting
confidence: 85%
“…Theoretical accounts of the disruptive nature of pain [14] and research showing that pain during a task impairs performance more than other stimuli (such as aversive non-tactile stimulation [16] or less aversive tactile stimulation [12,13,30]), imply that interruptions by pain produce worse outcomes than interruptions by non-painful stimuli. To date, however, direct evidence supporting this hypothesis is lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…the typical finding that performance is impaired when one switches from one activity to another, compared to continuing with the same activity. In the field of pain it has been shown that switching from a painful task to another activity imposes higher costs than switching from a non-painful task to another activity [38]. The second process involves retrieving from memory the information regarding the interrupted task [33].…”
Section: Resumption Lagmentioning
confidence: 99%